2014
DOI: 10.2494/photopolymer.27.61
|View full text |Cite
|
Sign up to set email alerts
|

Breakthrough Achievement In Nanoimprint Lithography Using PFP Condensable Gas

Abstract: The effectiveness of condensable gas, used as ambience, in UV nanoimprint lithography has been demonstrated. Bubble defect problem, which is inherent in UV nanoimprint under non vacuum ambience, can be solved by PFP condensable gas. UV nanoimprint lithography using PFP was validated for 45 nm pattern fabrication under thin residual layer conditions, which are required for UV nanoimprint used as UV nanoimprint lithography. PFP reduces the viscosity and demolding force of UV curable resins. These properties are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 55 publications
0
2
0
Order By: Relevance
“…UV nanoimprint lithography (UV-NIL) has been extensively investigated due to the fabrication of not only nanopatterning for microelectronics but also functional materials for micro-electro-mechanical systems (MEMS) [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17]. UV-NIL utilizes UV light to cure a photoresist which was pressed using a patterned master mold to obtain the patterned structures.…”
Section: Introductionmentioning
confidence: 99%
“…UV nanoimprint lithography (UV-NIL) has been extensively investigated due to the fabrication of not only nanopatterning for microelectronics but also functional materials for micro-electro-mechanical systems (MEMS) [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17]. UV-NIL utilizes UV light to cure a photoresist which was pressed using a patterned master mold to obtain the patterned structures.…”
Section: Introductionmentioning
confidence: 99%
“…A typical condensable gas used in the approach is 1,1,1,3,3-pentafluoropropane (PFP). It was reported that PFP can reduce the viscosity and separation force of UV curable resins and 20,000 repeated imprints with a single mold by UV imprint using PFP were successfully demonstrated [22]. However, influence of mixing of PFP and resist material should be discussed in terms of etching resistance of cured resist film.…”
Section: Introductionmentioning
confidence: 99%